Improving the energy resolution of bent crystal X-ray spectrometers with position-sensitive detectors - Honkanen, Ari-Pekka (J Synchrotron Radiat, 2014)
Wavelength-dispersive high-resolution X-ray spectrometers often employ elastically bent crystals for the wavelength analysis. In a preceding paper [Honkanen et al. (2014). J. Synchrotron Rad. 21, 104–110] a theory for quantifying the internal stress of a macroscopically large spherically curved analyser crystal was presented. Here the theory is applied to compensate for the corresponding decrease of the energy resolution. The technique is demonstrated with a Johann-type spectrometer using a spherically bent Si(660) analyser in near-backscattering geometry, where an improvement in the energy resolution from 1.0 eV down to 0.5 eV at 9.7 keV incident photon energy was observed.